Cohesins Determine the Attachment Manner of Kinetochores to Spindle Microtubules at Meiosis I in Fission Yeast - Yokobayashi, Shihori (American Society for Microbiology, 2003)
During mitosis, sister kinetochores attach to microtubules that extend to opposite spindle poles (bipolar attachment) and pull the chromatids apart at anaphase (equational segregation). A multisubunit complex called cohesin, including Rad21/Scc1, plays a crucial role in sister chromatid cohesion and equational segregation at mitosis. Meiosis I differs from mitosis in having a reductional pattern of chromosome segregation, in which sister kinetochores are attached to the same spindle (monopolar attachment). During meiosis, Rad21/Scc1 is largely replaced by its meiotic counterpart, Rec8. If Rec8 is inactivated in fission yeast, meiosis I is shifted from reductional to equational division. However, the reason rec8Δ cells undergo equational rather than random division has not been clarified; therefore, it has been unclear whether equational segregation is due to a loss of cohesin in general or to a loss of a specific requirement for Rec8. We report here that the equational segregation at meiosis I depends on substitutive Rad21, which relocates to the centromeres if Rec8 is absent. Moreover, we demonstrate that even if sufficient amounts of Rad21 are transferred to the centromeres at meiosis I, thereby establishing cohesion at the centromeres, rec8Δ cells never recover monopolar attachment but instead secure bipolar attachment. Thus, Rec8 and Rad21 define monopolar and bipolar attachment, respectively, at meiosis I. We conclude that cohesin is a crucial determinant of the attachment manner of kinetochores to the spindle microtubules at meiosis I in fission yeast.